Water, life & civilisation climate, environment, and society in the Jordan Valley - Mithen, Steven J.; Black, Emily (International hydrology series., 2011)
"A unique interdisciplinary study of the relationships between climate, hydrology and human society from 20,000 years ago to the present day within the Jordan Valley. It describes how state-of-the-art models can simulate the past, present and future climates of the Near East, reviews and provides new evidence for environmental change from geological deposits, builds hydrological models for the River Jordan and associated wadis and explains how present day urban and rural communities manage their water supply. The volume provides a new approach and new methods that can be applied for exploring the relationships between climate, hydrology and human society in arid and semi-arid regions throughout the world. It is an invaluable reference for researchers and advanced students concerned with the impacts of climate change and hydrology on human society, especially in the Near East"--